BURNOUT AMONG FARMERS IN ENUGU STATE, NIGERIA: THE ROLE OF ECONOMIC STRESS AND FARMING INSECURITIES - Aneke, Josephine (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
The contemporary agricultural ecosystem in Nigeria is consistently threatened by many factors, including the psychological condition of burnout. The present study examined farmers' burnout based on economic stress and farming insecurities in a sample of farmers recruited from different farming communities in Enugu state, Nigeria. Two hundred and fourteen respondents completed a self-report measure of economic stress and farming insecurity. Two hypotheses were tested using data from the respondents. Multiple regression was performed on the data, and the result demonstrated a statistically significant effect of economic stress and farming insecurity on farmers' burnout F (1,212), 24.34 P< .05. An observation of the R2 indicated that the independent variable explained about 18.8% of the variation in farmer's burnout. The study has implications for food production.